Proceso de atención de enfermería en paciente con diabetes gestacional. - Taípe Zurita, Mario Andres (2022)
Gestational diabetes is a type of diabetes that appears for the first time during pregnancy in pregnant women who have never had this disease before. In some women, gestational diabetes can affect them in more than one pregnancy. Gestational diabetes usually appears in the middle of pregnancy. Doctors usually do tests between 24 and 28 weeks of pregnancy. Gestational diabetes can often be controlled with healthy eating and regular exercise, but sometimes the mother will also need insulin. Gestational Diabetes occurs in 7% of all pregnancies worldwide and its incidence can vary between 1 and 14%, according to different ethnic factors typical of the region. In the Annual Epidemiological Notification System of the Ministry of Public Health of Ecuador, Gestational Diabetes shows a sustained increase in the period between 1994 and 2009, a notably more pronounced rise since 2017. The rate increased from 142 to 1084 cases, for per 100,000 inhabitants, with a higher prevalence in women on the Ecuadorian coast, especially in the province of Manabí. This phenomenon is repeated between 2009 and 2013. According to official statistics from the Ecuadorian Institute of Statistics and Censuses (INEC), Gestational Diabetes ranked sixth among the causes of maternal-fetal morbidity and mortality in 2009.